Taxonomy on three allied genera within Arcypterini (Orthoptera: Acrididae) from Qinghai-Xizang Plateau, China - Mao, Ben-Yong; Huang, Zhi-Pang (Zootaxa, 2023)
The generic diagnosis of three allied genera, Leuconemacris Zheng, 1988, Asulconotoides Liu, 1984 and Asulconotus Ying, 1974, are compared and redescribed. Four new species, Leuconemacris acuminata, sp. nov., L. xinlongensis, sp. nov., L. muliensis, sp. nov. and Asulconotus acarinatus, sp. nov. are described and illustrated. Two new combinations are established: Asulconotoides asulcata (Zheng, 1988) comb. nov. = Leuconemacris asulcata Zheng, 1988 and Asulconotoides microptera (Zheng, 1988), comb. nov. = Leuconemacris microptera Zheng, 1988. All updated keys to genera and species are given.